2021
DOI: 10.1159/000519797
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the Diagnosis and Severity of Presentation of Pediatric Type 1 and Type 2 Diabetes during the COVID-19 Pandemic

Abstract: Introduction:The impact of the COVID-19 pandemic on the incidence of pediatric type 1 (T1D) and type 2 diabetes (T2D) and severity of presentation at diagnosis is unclear. Methods: A retrospective comparison of 737 youth diagnosed with T1D and T2D during the initial 12 months of the CO-VID-19 pandemic and in the preceding 2 years was conducted at a pediatric tertiary care center. Results: Incident cases of T1D rose from 152 to 158 in the 2 years before the pandemic (3.9% increase) to 182 cases during the pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(104 citation statements)
references
References 36 publications
6
91
0
1
Order By: Relevance
“…Moreover, severity of initial presentation rose, based on proportion presenting with metabolic decompensation, which more than doubled, and median HbA1c at diagnosis. This confirms the findings of three single-center studies, all of which contributed data to this analysis, suggesting that rates of type 2 diabetes and presentation in DKA rose during the COVID-19 pandemic 11 , 14 , 15 .…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, severity of initial presentation rose, based on proportion presenting with metabolic decompensation, which more than doubled, and median HbA1c at diagnosis. This confirms the findings of three single-center studies, all of which contributed data to this analysis, suggesting that rates of type 2 diabetes and presentation in DKA rose during the COVID-19 pandemic 11 , 14 , 15 .…”
Section: Discussionsupporting
confidence: 87%
“…Twenty‐four studies 12 , 13 , 14 , 16 , 17 , 18 , 19 , 20 , 29 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 involving 5671 new T1D patients (2706 new T1D patients in 2019 and 2965 new T1D patients in 2020) reported numbers of pediatric new‐onset T1D before and after the COVID‐19 pandemic. Overall, the COVID‐19 pandemic was significantly associated with an increase in the number of worldwide pediatric newly diagnosed T1D (logit ER = 0.080, 95% confidence interval [CI] 0.028–0.133, p = 0.003; Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one studies 12 , 13 , 14 , 16 , 18 , 19 , 20 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 involving 2648 new T1D patients with DKA and 979 new T1D patients with severe DKA (DKA: 1177 new cases in 2019 and 1471 new cases in 2020; severe DKA: 446 new cases in 2019 and 533 new cases in 2020) were included. The random‐effect model showed that COVID‐19 pandemic was associated with an elevation in the risk incidence of worldwide pediatric DKA and severe DKA compared with pre‐COVID‐19 period (RR = 0.064, 95% CI 0.043– 0.084, p = 0.0001, and RR, 0.049 (95% CI: 0.029–0.066; p = 0.0001, respectively; Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] An increase in newly diagnosed T1D has been posited during the COVID-19 pandemic. However, published reports have shown conflicting findings, with some reports suggesting an increase in newly diagnosed T1D in children and adolescents, [13][14][15] and others showing no change in expected or actual numbers of newly diagnosed T1D. 16,17 Our objective for this study was to describe trends in newly diagnosed T1D, as well as the severity of presentation at diagnosis during COVID-19 compared to the prior year using data from seven large U.S. clinical centers.…”
Section: Introductionmentioning
confidence: 99%